Pembentukan Tradisi Ilmiah Dalam Islam Dan Hubungannya Dengan Worldview Islam Dalam Pandangan Muhammad Naquib Al-Attas - Muhammad Azrul Amirullah; Muhammad Ridwan Mubarok; Maulana At-Tsani (Ma'had Aly Journal of Islamic Studies, 2026)
Islam is a perfect religion. To understand Islam, knowledge based on the values of the Qur'an and the guidance of the Prophet Muhammad (peace be upon him) is needed to form an Islamic perspective. Muhammad Naquib Al Attas has declared this to prevent what is called westernization or western thought patterns that arise and spread in Islamic traditions and perspectives. In fact, Muslims must study what has become their scientific tradition (Islam) to be distanced from the values of westernization. In this writing, a normative approach is used based on facts and written data sources in the form of journals, articles, and books that have a relationship to this discussion. As a result, Muhammad Naquib Al Attas emphasized the importance of the Islamization of knowledge as a bridge to prevent western perspectives or worldviews, which refers to Islamic epistemology, namely the Qur'an and the guidance of the Prophet Muhammad (peace be upon him). Muhammad Naquib Al-Attas also urged Muslims to sort out contemporary science, which has been mixed with Western speculation and ideology that contradict Islamic values. He offered a solution that focuses on reconstructing contemporary science by integrating Islamic values and worldview (tawhid) as its epistemological basis, not only methodologically, but also in terms of values, goals, and ethics.